Profil Pelaksanaan Pembelajaran Berdiferensiasi di SMK Negeri 3 Jepara - Latifah, Nur; Roshayanti, Fenny; Hayat, Muhammad Syaipul; Khoiri, Nur (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
This study aims to determine the implementation of differentiated learning at SMK Negeri 3 Jepara. This type of research is qualitative research. Interview, survey and documentation methods were chosen as data collection techniques. The results of data collection were analyzed using data triangulation. In carrying out the research at SMK Negeri 3 Jepara, 42 teachers were involved as respondents who were selected randomly. From the survey results, information was obtained that 80.96% of teachers had heard of differentiated learning. 71.42% of teachers have understood the concept of differentiated learning, 60% better understand the application of differentiated learning strategies, but only 33.33% of teachers carry out differentiated learning. 52.38% of teachers consider differentiated learning to support student characteristics, but the teacher's workload increases. 71.43% still think that the application of differentiated learning requires more time in learning activities. Another fact based on interviews found that there were still a few teachers who carried out differentiated learning because they found many obstacles in its implementation, including difficulties in making the tools, especially student worksheets (LKPD).